Gender and Enterprise Development in Sub-Saharan Africa : A Review of Constraints and Effective Interventions - Campos, Francisco; Gassier, Marine (World Bank, Washington, DC, 2017)
Female participation in entrepreneurial activities is higher in Sub-Saharan Africa than in any other region. However, women-owned businesses significantly underperform those owned by men. This paper identifies the main constraints that women face in developing their businesses in Africa and discusses how these constraints influence strategic choices in areas such as level of investment and sector of operations. The paper synthesizes the emerging lessons about what works and what does not work to address the underlying constraints to the performance of women-owned firms. Moreover, it identifies knowledge gaps and priority research questions. The paper aims to support the development of a gender-informed policy and research agenda on enterprise development that can guide practitioners, development partners, and researchers who seek to advance women's economic empowerment in Africa.